PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP COST OF DEBT PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Calen Calen (Jurnal Ekonomi dan Bisnis (EK&BI), 2019)
This study aims to determine the influence of the Good Corporate Governance either partially or simultaneously on Cost of Debt in Retail Companies are listed on Indonesia Stock Exchanges. Population in this study, are Retail Company in Indonesia which is listed on Indonesia Stock Exchanges since 2009 until 2013 as much as 15 companies with the samples taken by purposive sampling as much as 13 companies. Collected data is secondary data. Prior to data analysis, first tested data analysis is classical assumption test such as normality test, multicollinearity test, heteroscedasticity test, and autocorellation test. Methode of data analysis used is multiple linear regression with 95% assurance level. The results of this study indicate that the partial effect and simultaneously, Good Corporate Governance doesn’t have any effects to Cost of Debt.